2009
DOI: 10.1111/j.1467-985x.2009.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Shortages, Teacher Contracts and Their Effect on Education in Africa

Abstract: To enhance primary enrolment rates, many African countries have launched large teacher recruitment programmes in recent years. Given tight budgetary constraints, teachers are no longer employed in civil service positions, but on the basis of (fixed term) contracts typically implying considerably lower salaries and a sharply reduced amount of professional training. We analyse the effect of this change on educational quality in Niger, Togo and Mali, on the basis of very informative data, which are comparable acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…(2005) suggest that students of regular teachers clearly outperform those of contract teachers, and Bourdon et al (2006) argue that contract teachers may deteriorate education quality. On the other hand, Bourdon et al (2007) suggest that contract teachers may have a positive impact, although they do find negative impacts when it is implemented in a more centralized manner. In addition to these studies, Goyal and Pandey (2009) report that contract teachers consistently demonstrated higher effort than regular teachers.…”
mentioning
confidence: 86%
“…(2005) suggest that students of regular teachers clearly outperform those of contract teachers, and Bourdon et al (2006) argue that contract teachers may deteriorate education quality. On the other hand, Bourdon et al (2007) suggest that contract teachers may have a positive impact, although they do find negative impacts when it is implemented in a more centralized manner. In addition to these studies, Goyal and Pandey (2009) report that contract teachers consistently demonstrated higher effort than regular teachers.…”
mentioning
confidence: 86%
“…In particular, these studies have focused on the effects of the recruitment of local contract teachers (see e.g. Atherton and Kingdon, 2010;Bourdon et al 2010;de Laat and Vegas, 2005;Duflo et al 2012 andSundararaman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on contract teachers in other developing countries produce somewhat more mixed results (see e.g. Bourdon et al 2010, de Laat and Vegas, 2005). 14 The Uttarakhand BTC application data is publicly available, and entrance test marks of applicants are somewhat lower for women than for men.…”
mentioning
confidence: 99%
“…Another study that relied on matched comparisons between contract teachers with observationally similar civil servants in Mali, Togo, and Niger, found mixed results, with positive, null, and negative effects on student test scores in those countries, respectively [6].…”
Section: Contract Teachersmentioning
confidence: 99%
“…Salaries for certified teachers represent approximately two-thirds of this amount [6]. Civil service teachers, who are usually certified, earn between 1.2 and five times the salaries of contract teachers, who are often uncertified, across several countries for which there is data ( Figure 2).…”
Section: Teachers In Developing Countriesmentioning
confidence: 99%